University–Industry Linkages in Promoting Technical Skills for Human Resource Development, Case Study of Thailand - Quynh Huong Nguyen (IKAT: The Indonesian Journal of Southeast Asian Studies, 2022)
Labor productivity is an important goal for national sustainable development. Thailand has a potential labor force and attracts significant foreign direct investment, especially from Japan. This research paper presents the current situation of labor productivity in Thailand and discusses how to upgrade the technical know-how for Thai engineering students through technical assistance from Japanese organizations and firms. This paper argues that the labor productivity of Thailand cannot boost the workforce’s skill without cooperation with foreign firms and organizations (Japanese ones in this case). This paper also raises the issue of university-industry linkages, which require comprehensive strategic cooperation between theory-based education and technical training, all of which contributes to the quality and adaptability of the labor force. This is a qualitative study based on interviews with Japanese organizations, Japanese firms, and universities in Thailand on how to enhance the technical skills of the labor force in the manufacturing industry. The paper uses a case study of Thai-Nichi Institute of Technology (TNI), which describes the training and “learning by doing” methods to upgrade the technical skills of the Thai workforce.